2018
DOI: 10.3390/ma11020185
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Density Electropulsing to Improve the Performance of Metallic Materials: Mechanisms, Microstructure and Properties

Abstract: The technology of high-density electropulsing has been applied to increase the performance of metallic materials since the 1990s and has shown significant advantages over traditional heat treatment in many aspects. However, the microstructure changes in electropulsing treatment (EPT) metals and alloys have not been fully explored, and the effects vary significantly on different material. When high-density electrical pulses are applied to metals and alloys, the input of electric energy and thermal energy genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 146 publications
(203 reference statements)
3
20
0
1
Order By: Relevance
“…Previous studies [25,26] have indicated that heavily cold worked metals could be subdivided by grain boundaries and dislocation boundaries. The cold work inducing the formation of the grain boundary was also found in CR AZ91 alloy [27] and 308L stainless steel [28]. In this 316LN ASS, in addition to dislocation grain boundaries, the boundaries of mechanical twins and strain-induced martensite formed during the CR process can also subdivide untransformed austenite, leading to the decrease of the untransformed austenite structure size.…”
Section: The Effect Of Cold Deformation On the Microstructuresmentioning
confidence: 73%
“…Previous studies [25,26] have indicated that heavily cold worked metals could be subdivided by grain boundaries and dislocation boundaries. The cold work inducing the formation of the grain boundary was also found in CR AZ91 alloy [27] and 308L stainless steel [28]. In this 316LN ASS, in addition to dislocation grain boundaries, the boundaries of mechanical twins and strain-induced martensite formed during the CR process can also subdivide untransformed austenite, leading to the decrease of the untransformed austenite structure size.…”
Section: The Effect Of Cold Deformation On the Microstructuresmentioning
confidence: 73%
“…In addition, due to the repulsion effect, the distance between inclusions (e.g., the inclusions M and N in Figure b) is greater than that of the untreated sample (Figure a). In fact, the electric current affects many other second phases whose conductivity are different from that of matrix . Electric current causes the fragment of lamellar cementite to be perpendicular to current .…”
Section: Resultsmentioning
confidence: 99%
“…hence, a change in the residual stresses of the single phase was expected [30,[50][51][52][53]. An increase in compression stress amounts in ferrite after the first electropulsing treatment was determined and this did not change even after the electropulsing treatment at higher current density and higher number of pulses (Figure 16a).…”
Section: Residual Stressesmentioning
confidence: 87%
“…Since tensile test introduces uniaxial stress configuration in the specimen, no variation in the average residual internal stresses was expected. On the other hand, electropulsing treatments have shown to induce changes in the grain orientation within the materials not to mention the change in morphology of secondary low conductivity phases (i.e., cementite particles in perlite) hence, a change in the residual stresses of the single phase was expected [30,[50][51][52][53]. An increase in compression stress amounts in ferrite after the first electropulsing treatment was determined and this did not change even after the electropulsing treatment at higher current density and higher number of pulses (Figure 16a).…”
Section: Residual Stressesmentioning
confidence: 99%